2020
DOI: 10.3389/fendo.2020.516213
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of MicroRNAs in Human Osteoporosis

Abstract: MicroRNAs (miRNAs) are single-stranded RNA molecules that control gene expression in various processes, such as cancers, Alzheimer's disease, and bone metabolic diseases. However, the regulatory roles of miRNAs in osteoporosis have not been systematically analyzed. Here, we performed a comprehensive analysis to identify the differentially expressed miRNAs involved in osteoporosis. MiRNAs associated with osteoporosis were collected through literature retrieval and further screened based on specific inclusion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Here, we further confirmed that miR-138-5p was elevated with age and negatively correlated with osteoblast differentiation and osteogenesis in human tissues, mice and cultured cells (Figure 1 ). In our previous study, we screened and identified several miRNAs, including miR-138-5p, as potential biomarkers or therapeutic targets in human osteoporosis 14 , 34 , 35 . These data suggested that miR-138-5p might play an important role in senile osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we further confirmed that miR-138-5p was elevated with age and negatively correlated with osteoblast differentiation and osteogenesis in human tissues, mice and cultured cells (Figure 1 ). In our previous study, we screened and identified several miRNAs, including miR-138-5p, as potential biomarkers or therapeutic targets in human osteoporosis 14 , 34 , 35 . These data suggested that miR-138-5p might play an important role in senile osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study reported that miR-155 levels are significantly upregulated in human OA cartilage biopsies and primary chondrocytes stimulated by IL-1ß. Moreover, miR-155 overexpression promotes IL-1ß-induced apoptosis and catabolic activity in chondrocytes in vitro (159). Chen et al reported that MSC-sEV-shuttled miR-136-5p promotes chondrocyte migration in vitro and inhibits cartilage degeneration in vivo (Figure 1) both in human chondrocytes in vitro and in mice in vivo (160).…”
Section: Mirna Shuttled By Sevs Derived From Mscs and Their Therapeutic Function On Osteoarticular Diseasesmentioning
confidence: 99%
“…In contrast, another study reported that miR-155 levels are significantly upregulated in human OA cartilage biopsies and primary chondrocytes stimulated by IL-1ß. Moreover, miR-155 overexpression promotes IL-1ß-induced apoptosis and catabolic activity in chondrocytes in vitro ( 159 ). Chen et al.…”
Section: Mirna Shuttled By Sevs Derived From Mscs and Their Therapeutic Function On Osteoarticular Diseasesmentioning
confidence: 99%
“…The consequences of osteoporosis substantially increase the consumption of medical and economic resources worldwide (3). Until now, many expression profiling studies have revealed that bone remodeling processes are well-tuned at the transcriptional level and controlled by noncoding RNAs, especially long non-coding RNAs and microRNAs (miRNAs) (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%